Learning strategies to develop english pronunciation for second basic grade students at escuela de educación básica José Mejía Lequerica, José Luis Tamayo, Salinas, province of Santa Elena school year 2015-2016. - De La A Salinas, Diana Liccete (2016)
English pronunciation is very important for students, and it can be developed through the implementation of English learning strategies. Effective strategies like songs can motivate students to learn the correct pronunciation of English words in an enjoyable way. Children need to listen to the pronunciation of the English words and to listen to the rhythm of the music. They can get involved and interested in learning a new language. The purpose of this research is to implement teaching activities that contain strategies for children to develop the correct pronunciation of English words. Students will feel motivated to learn the pronunciation of words, to assimilate the sounds of vowels and consonants according to their level of learning. In the schools teachers should employ learning strategies that can help the students improve the pronunciation of the English language.